Fluid-induced, shear stress-regulated extracellular matrix and matrix metalloproteinase genes expression on human annulus fibrosus cells. Issue 1 (December 2016) - Chou, Po-Hsin; Wang, Shih-Tien; Yen, Meng-Hua; Liu, Chien-Lin; Chang, Ming-Chau; Lee, Oscar
Abstract Background Mechanical loading plays an important role in the regulation of extracellular matrix (ECM) homeostasis as well as pathogenesis of intervertebral disc (IVD) degeneration. The human annulus fibrosus (hAF) in the IVD is subjected to contact shear stress during body motion. However, the effects of shear stress on hAF cells remain unclear. This aim of the study was to investigate the expression of the ECM (COLI, COLIII andaggrecan ) and matrix metalloproteinase (MMP-1, MMP-3 andADAMTS-4 ) genes in hAF cells following fluid-induced shear stress in a custom-fabricated bio-microfluidic device. Methods hAF cells were harvested from degenerated disc tissues in routine spine surgery, staged by magnetic resonance imaging, expanded in monolayers and then seeded onto the bio-microfluidic device. The experimental groups were subjected to 1 and 10 dyne/cm2 shear stress for 4 h, and no shear stress was applied to the control group. We used real time polymerase chain reaction for gene expression. Results Shear stress of 1 dyne/cm2 exerted an anabolic effect onCOLI andCOLIII genes and catabolic effects on theaggrecan gene, while 10 dyne/cm2 had an anabolic effect on theCOLI gene and a catabolic effect onCOLIII andaggrecan genes. TheCOLI gene was upregulated in a stress-dependent manner. Expression ofMMP-1 was significantly higher in the 10 dyne/cm2 group compared to the control group (P  < 0.05), but was similar in the control and 1 dyne/cm2 groups. Expression ofMMP-3 andADAMTS-4 were similar in all three groups. Conclusion Taken together, hAF cells responded to shear stress. The findings help us understand and clarify the effects of shear stress on IVD degeneration as well as the development of a new therapeutic strategy for IVD degeneration.